The Influence of Liquidity, Leverage, Profitability and Business Risk on the Dividend Policy of Manufacturing Companies listed on the IDX - Eskasari Putri; Bunga Naifa Ardiningrum; Nursiam Nursiam (Riset Akuntansi dan Keuangan Indonesia, 2022)
Dividend policy concern the issue of the use of profits that are the right of sharelohders, these profits can be divided as dividends or held for reinvestment. This study aims to determine the effect of liquiditu, leverage, profitability, and business risk on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The population in this study are manufacturing companies totaling 116 companies. The sampling technique used was purposive sampling so as to obtain as many as 40 samples of companies in rhe food and beverage sub-sector manufacturing companies. The data collection method used s documentary data, with data in the form of financial reports obtained from www.idx.co.id. The data analysis technique used is multiple linear regression. Based on the result of the analysis, it shows that partially liquidity and profitability have a significant negative effect on dividend policy, while leverage and business risk have a significant positive effect on dividend policy in manufacturing companies on Indonesia Stock Exchange for the 2016-2019 period.